The spectral structure of vocalizations match hearing sensitivity but imprecisely in Philautus odontotarsus. Issue 2 (4th May 2017) - Zhu, Bicheng; Wang, Jichao; Brauth, Steven E.; Tang, Yezhong; Cui, Jianguo
Abstract: It is generally thought that for species using vocal communication the spectral properties of the sender's calls should match the frequency sensitivity of the receiver's auditory system. Nevertheless, few studies have investigated both sender and receiver characteristics in anuran species. In the present study, auditory brainstem responses (ABRs) were recorded in the serrate legged treefrog, Philautus odontotarsus, in order to determine if male call spectral structure and hearing sensitivity in males and females have co-evolved in this species. The results showed that the spectral structures of male vocalization match both male and female hearing sensitivity, even though the dominant frequencies of male calls (2.5 kHz) are mismatched with the regions of best frequency sensitivity (1.4 and 2.8 kHz). In addition, the results show that, in contrast with most previous ABR studies in non-human animals, but consistent with human studies, there are noticeable sex differences in peripheral auditory sensitivity in Philautus insofar as females exhibit lower auditory thresholds than males across the entire 1.8–18 kHz frequency range. The results also show that the dominant frequency of male calls is negatively correlated with body size, indicating that call characteristics reflect body size in this species which may be used by females during mate choice.